We are playing relatives a survey of Malay writing - Maier, Hendrik M.J (Institute of Southeast Asian Studies, 2004)
We are playing relatives offers a comprehensive survey of literature writing in the malay language. It starts with the playful evocations of language and reality in the Hikayat hang Tuah, a work that circulated on the Malay Peninsula in the eighteenth century, and follows the Malay literary impulse up to the beginning of the twenty-first century, a time when the dominant notions of Malay literature seem to fade away in the cyberspace created on the island of Java, and the Hikayat Hang Tuah's play and dance on the sounds of Malay words seem to be infused with a new vitality.--Cover